Study the Influence of Smoking on Level of Selected Pentraxin (PTX s) and Tumor Necrosis Factor Alpha (TNF-α) in Saliva of Cigarette Smoker Patients with Chronic Periodontitis - Doaa Adil Abood (Journal of Global Pharma Technology, 2019)
Background: Pentraxin (PTX s) is a classical mediator of inflammation and super family of a cut – phase proteins. Tumor necrosis factor-α, is one of the pro-inflammatory cytokines, released in various chronic inflammatory disease including periodontitis. Subjects and method: the study comprised 75 patients,50 with chronic periodontitis (CP) (25 smoker and 25 non smoker ) and 25 normal subjects, age ranged between (20-50 years old, This study carried out in periodontal department clinic/ collage of dentistry/ university of Babylon, Hilla city , Iraq, 5 ml of unstimulated whole saliva was collected from all subjects to measure Pentraxin-3(PTX-3) and tumor necrosis factor (TNF-α) by Enzyme-linked immunosorbent assay technique (ELISA).Result: the result show there are non-significant differences in the levels of PTX-3 and TNF-α between the patients and controls and non significant between smoker and non smoker(p≤ 0.05) .In smoker patients there is a negative correlation between concentration PTX-3 and number of cigarette per years of smoking. While there’s a positive correlation between level of TNF-α and and number of cigarette per years of smoking. Conclusion: Smoking in chronic periodontitis patients has no effects on levels of PTX-3 and TNF-α in saliva.Keywords: Chronic periodontitis, Smoking, Saliva, PTX-3, TNF-α.